2018
DOI: 10.1111/pce.13119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic modelling of limitations on improving leaf CO2 assimilation under fluctuating irradiance

Abstract: A dynamic model of leaf CO assimilation was developed as an extension of the canonical steady-state model, by adding the effects of energy-dependent non-photochemical quenching (qE), chloroplast movement, photoinhibition, regulation of enzyme activity in the Calvin cycle, metabolite concentrations, and dynamic CO diffusion. The model was calibrated and tested successfully using published measurements of gas exchange and chlorophyll fluorescence on Arabidopsis thaliana ecotype Col-0 and several photosynthetic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 94 publications
(176 reference statements)
1
60
0
Order By: Relevance
“…Mechanistic models of photosynthesis combined with NPQ limitations will need to be combined with methodologies that allow for the measurement of fluctuations of light in space within canopies. Dynamic empirical and mechanistic models of photosynthesis capable of handling light fluctuations are available and can be applied to the light fluxes from canopy imaging studies (Porcar‐Castell et al , ; Retkute et al , ; Harbinson and Yin, ; Morales et al , ; Townsend et al , ,b,c)). Models of individual processes that form NPQ are also becoming more sophisticated (Zaks et al , ).…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%
“…Mechanistic models of photosynthesis combined with NPQ limitations will need to be combined with methodologies that allow for the measurement of fluctuations of light in space within canopies. Dynamic empirical and mechanistic models of photosynthesis capable of handling light fluctuations are available and can be applied to the light fluxes from canopy imaging studies (Porcar‐Castell et al , ; Retkute et al , ; Harbinson and Yin, ; Morales et al , ; Townsend et al , ,b,c)). Models of individual processes that form NPQ are also becoming more sophisticated (Zaks et al , ).…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%
“…In relation to plant physiology, our representation of plant responses includes the essential response to light, temperature, and water vapor changes. However, we foresee that future plant physiological studies can improve this description of these responses at the leaf level (e.g., Morales et al, 2018), as well as the spatial distribution of stoma in the leaf to improve the gas exchange (de Boer et al, 2016).…”
Section: Moving Forward In Land-atmosphere Interaction Studiesmentioning
confidence: 99%
“…This has been further demonstrated in Arabidopsis plants that lack functional genes involved in photoprotection and light adaptation, such as in the PsbS npq4‐1 (Li et al ., ) and glucose 6‐phosphate / phosphate translocator 2 ( gpt2 ) (Athanasiou et al ., ) mutants. Improvement of regulatory processes and adaptation mechanisms that allow plants to improve their physiological responses to fast and slow changes in light availability is highlighted as a promising path for improvement of crop photosynthetic efficiency (Long et al ., ; Kromdijk et al ., ; Taylor and Long, ; Morales et al ., ).…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 97%
“…Long‐term light fluctuations include changes in weekly weather conditions and even seasonal variation, which affect plant development and photosynthetic efficiency. Recent insights into mismatches between incoming light and the ability to put that energy into use in carbon assimilation as a result of light fluctuations showed that these can cause considerable growth penalties and reduction in photosynthetic carbon assimilation in photoautotrophic organisms (Zhu et al ., ; Graham et al ., ; Vialet‐Chabrand et al ., ; Taylor and Long, ; Morales et al ., ; Slattery et al ., ). This has been further demonstrated in Arabidopsis plants that lack functional genes involved in photoprotection and light adaptation, such as in the PsbS npq4‐1 (Li et al ., ) and glucose 6‐phosphate / phosphate translocator 2 ( gpt2 ) (Athanasiou et al ., ) mutants.…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 98%